クレイシ ケイセイ キ ニ オケル アデリー ペンギン シュウダン ノ ケイジ テキ ヘンカ - 青柳, 昌宏; アオヤナギ, マサヒロ; Aoyanagi, Masahiro (1988)
P(論文) 1978-79年夏期, ロス島ケープバード, 北ルッカリーのB4コロニーにおいて, アデリーペンギン集団の経時的変化を観察した。1978年12月下旬から予備調査を行い, 1979年1月1日から1月24日までの間, 少なくとも1日1回, コロニー内の繁殖巣数, 繁殖個体数, 未繁殖個体数, 雛数, およびその位置を観察し地図上に記録した。この時期は雛のクレイシ形成期であり, 繁殖個体が巣を離れるのに従って, 雛も巣を離れクレイシを形成した。1月9日から10日の間に, 繁殖個体と雛の巣離れが完了した。同時に, これまでコロニーの外にいた未繁殖個体が繁殖個体に代わってコロニーに入った。巣を離れた雛はクレイシのところどころに密集し小集団を造ったが, その大きさ, 形, 場所は常に変化した。クレイシ形成の初期に雛は元の巣に戻って給餌を受けたが, 次第に巣の外で給餌されるようになり, 1月10日以後はコロニーの外で給餌を受けるようになった。 The temporal change of an Adelie penguin population was observed in the B4 colony, Northern Rookery, Cape Bird, Ross Island in the 1978-79 summer season. Between January 1 and 24,1979,after the preparatory observation in late December, the number and position of occupied nests, occupying birds, re-occupying nonbreeders and chicks were observed and recorded on a map at least once a day. Upon abandonment of the nests by the occupant birds, the chicks left their nests to form a creche in the colony. The nest abandonment and the creche formation were completed on January 9 and 10. Simultaneously, the free-nonbreeders entered the colony from the outside of it. Part of the chicks that left their nests gathered closely to form huddles in the creche. The size, shape and position of the huddles varied temporally. The feeding place of chicks changed from their nests to the outside of the nests and then to the outside of the colony with the progress of creche formation. departmental bulletin paper